WAKAF DALAM PERSPEKTIF FIKHI DAN HUKUM NASIONAL - Sesse, Muh. Sudirman (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2010)
Waqf is one of philanthropy institutions in Islam. Debates on which have been coloring of dynamical thought of Islam law, occurred since classical Islamic scholar until modern one. Topics is concerning with existenie of waqif, mauquf âalaih (nadzir), mauquf (object), and sighat (proclamation). Fiqh and Indonesian rule, called UU (red. Act) are giving deepest attention and analysis. The latest makes combination and accommodation to reconstruct and widen of the implementation scope of waqf. It is due to reinterpretation derived from earliest concept, and public welfare reached is as final objeitive of its philanthropy based on new interpretation. This paper is also going to elaborate some new issues like cash waqf (waqf al-nuqud) and productive waqf, emerged from lack of propessionalism and mismanagement of waqf object. Tese elaborations presented to analysis content substance of the Act 41/2004 as compromised solution conducted by the Rule.